Fungal diseases at the medical front door. (2nd March 2019) - Wilson, Aline; Wilkie, Morven; Rae, Nikolas
Abstract : Fungal diseases are an increasingly recognized cause of mortality worldwide and often pose diagnostic challenges. This article focuses on common fungal diseases as they may present in the acute medical unit, looking at the initial investigation and management of four common diseases: Pneumocystis jirovecii pneumonia, cryptococcal meningitis, candidaemia and allergic bronchopulmonary aspergillosis. There is an increase in morbidity and mortality if these conditions are not correctly diagnosed and thus appropriate therapy is delayed. A better understanding of the initial investigation and management of these conditions will improve the outcome of patients with fungal diseases presenting to the 'medical front door'.